DYNAMIC MAGNETIC RESONANCE IMAGING: AN AID TO PREOPERATIVE-PLANNING OF PELVIC ORGAN PROLAPSE - Memon, Bakhtawar; Shoukat, Shaista; Sultana, Nimrah; Parveen, Tahira; Fatima, Nasreen; Mehmood, Tariq (Journal of Ayub Medical College Abbottabad, 2021)
Background: Magnetic resonance imaging (MRI) has been commonly used in the assessment of pre-operative pelvic organ prolapse to evaluate anatomical defects prior to surgery. This study aimed at evaluating the dynamic MRI reliability in the determination of pelvic organ prolapse and to assess its compliance with the physical examination for preoperative planning of women. Methods: A prospective cross-sectional study was performed at the radiology department of the Jinnah Postgraduate Medical Centre Karachi from April-October 2019. All women irrespective of age and parity status having obstructed defecation, constipation, organ prolapse, pelvic pain, or stress urinary incontinence undergoing dynamic pelvic MRI were consecutively enrolled. A brief history was obtained followed by a physical examination for pelvic organ prolapse followed by MRI examination. Kappa coefficient was applied to see the agreement of physical examination with MRI finding. Results: A total 38 women were included. A significantly moderate agreement was observed between MRI and physical exam findings with respect to the presence or absence of cystocele (K=0.554, p<0.001), rectocele (K=0.632, p<0.001), and enterocele (K=0.587, p<0.001). However, agreement with respect to the MRI and physical examination findings on uterine descent was non-significant (K= 0.130, p 0.421). Conclusion: MRI examination is an effective diagnostic modality in determination of the pelvic organ prolapse in suspected symptomatic patients. MRI could add value primarily in research areas, taking into account its ability to examine the entire pelvis. Conclusion MRI examination is an effective diagnostic modality in determination of the pelvic organ prolapse in suspected symptomatic patients. Keywords Pelvic organ prolapse, dynamic magnetic resonance imaging, physical examination